Criticizing the Verdict of 916/Pdt.P/2022/PN.Sby Surabaya District Court Against Interfaith Marriage from the Perspective of Marriage Law in Indonesia - Fernanda, Ahmad; Azwar, Zainal; Ismail, Dailani (Hukum Keluarga Islam IAIN LANGSA, 2023)
This article is based on a critical review of the verdict of 916/Pdt.P/2022/PN.Sby, which recognizes the validity of interfaith marriages in Indonesia. This decision is different from the provisions of the marriage law in force in Indonesia. Indonesia has regulated that marriages can be carried out according to their respective religions. This article aims to critically analyze the verdict of 916/Pdt.P/2022/PN.Sby. This research is a normative juridical study with a case approach. The main data sources are obtained from court decisions and marriage laws. This article also uses several important articles and research resulting from empirical studies. Based on the data findings and analysis that have been carried out, this paper argues that: Firstly, interfaith marriages are prohibited in Islamic law because they contain more harm than good; this prohibition merely closes the opportunity for bad impacts to occur after the marriage; and second, the decision issued by the Surabaya District Court Judge was inappropriate because it conflicted with positive law and Islamic law. Legally, the judge may refuse to grant permission based on Article 2 paragraph (1) of the Law on Marriage and the Compilation of Islamic Law (KHI). In this decision, the judge has a different interpretation of the marriage regulations that apply in Indonesia.